Basel Accord and Banking Competitivity - Jebali, Lassaad; Hmedi, Siwar (Journal of Asian Business Strategy, 2016)
The first Basel Accord 1988 focused on the adoption of fixed minimum capital requirements, which led some banks to maintain higher capital ratios than they deserve some other banks succeeded in limiting risk-taking relative to capital as intended. Banks which didn’t succeed the risk management have been able to take actions to reduce their effectiveness, either by shifting to riskier assets within the same weighting band or through capital arbitrage. It looks at two possible side effects. Firstly, whether in some periods capital requirements may have had the effect of constraining bank lending thereby causing a credit crunch. Secondly, the introduction of fixed minimum requirements for banks affected competitiveness with relative forms of intermediation.